A Practical Approach to Lighting Design Course in an Electrical Engineering Programme - Valdez, Manuel Travassos; Agreira, C. I. Faustino; Ferreira, C. Machado; Barbosa, F. P. Maciel (International Journal of Emerging Technologies in Learning (iJET), 2008)
Technology has allowed new insights and creativity into the learning and teaching process and also enables to try out in a much more flexible, dynamic way other learning experiences. This constitutes in itself a more engaging role for teachers as well as students helping them to explore and create new areas, opening up, at the same time, new perspectives into the process and maximizing the availability and use of the current tools which the same technology provides. The facilitation in the investigation work development of projects renders the learning and teaching activities really appealing, allowing at the same time levels of effectiveness in this extremely modern and global era. This study integrates technology in the learning process and evaluation of its various outcomes. This case study describes the experience of two teachers with their class along a semester using computer aided technology for instruction and assessment. The task involved the lighting design of monuments with the purpose of attracting the on lookersâ?? attention, enhancing the beauty and attributes of the façade of monuments or buildings considered relevant or of public interest. An approach of reinforcement learning applied to the historical monuments light configurations will be described.